Improvement of Wastewater Treatment In Textile Production (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
At the enterprises of textile industry water is used as a solvent (for preparation of dyeing, bleaching and finishing solutions and washing of materials after their processing), extractant and cooling agent. About 70% of water consumed by the production is used for washing of raw materials and semi-finished products at different stages of the technological process. In this regard, wastewater generated at the enterprises can be divided into two groups:       concentrated - these are various spent process solutions, which contain the main amount of contaminants;       wash waters - the volume of these waters is many times higher than the volume of concentrated wastewater.